2011
DOI: 10.1080/17421772.2010.540035
|View full text |Cite
|
Sign up to set email alerts
|

Long and Short Distance Migration in Italy: The Role of Economic, Social and Environmental Characteristics

Abstract: This paper analyses Italian interregional migration flows. The approach taken is to decompose labour mobility flows into short distance and long distance migration and to model the effects of economic variables, social capital and quality of life variables, and amenity variables, on the mobility behaviour of individuals. We estimate these different types of migration flows using a negative binomial model, augmented with instruments to control for potential endogeneity issues. Our findings demonstrate that long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 60 publications
(61 reference statements)
7
140
3
3
Order By: Relevance
“…Antolin and Bover (1997) conclude that the unemployment rate has no significant effect on international migration and show that emigration occurs from regions where wages are higher than the average, which seems to contradict many of the theoretical findings. These conflicting conclusions are not only observed for the case of Spain, since Italian internal migrations do not react to mass unemployment, as Fachin (2007) found, nor to an increase in GDP, as determined by Biagi and Faggian (2011). Figure 1 shows the evolution of gross internal emigration and the unemployment rate, in the extended period 1988-2010, confirming that the lower the unemployment rate in Spain, the higher the interregional gross migration rate.…”
Section: Introductionmentioning
confidence: 64%
“…Antolin and Bover (1997) conclude that the unemployment rate has no significant effect on international migration and show that emigration occurs from regions where wages are higher than the average, which seems to contradict many of the theoretical findings. These conflicting conclusions are not only observed for the case of Spain, since Italian internal migrations do not react to mass unemployment, as Fachin (2007) found, nor to an increase in GDP, as determined by Biagi and Faggian (2011). Figure 1 shows the evolution of gross internal emigration and the unemployment rate, in the extended period 1988-2010, confirming that the lower the unemployment rate in Spain, the higher the interregional gross migration rate.…”
Section: Introductionmentioning
confidence: 64%
“…The existing empirical evidence on Europe, despite the tendency of most studies to stress the prevailing importance of economic factors (see for instance Cheshire and Magrini 2006;Faggian and McCann 2009;Ritsilä and Ovaskainen 2001), has recently suggested that quality of life, tolerance and local 'creativity' also play an important role for urban (Faggian and Royuela 2010) and inter-regional (Biagi et al 2011) European migration. Non-economic factors play a key role also in explaining European migration flows: network effects and regional socio-environmental conditions exert a significant influence over the locational choice of migrants (Rodríguez-Pose and Ketterer 2012).…”
Section: Where To Go After Graduation? Jobs Creative and Tolerant Plmentioning
confidence: 99%
“…For all these reasons, the assumption that the functional form is similar between long-and short-distance moves may not be reasonable. In fact, a recent study in Italy found differences in long-distance versus short-distance moves, concluding that whereas short distance moves reflect an equilibrium model, long distance moves reflect a disequilibrium model (Biagi, Faggian, and McCann 2011). A second limitation is that such research based on aggregate flows cannot account for the individual motivations and determinants that lead to such moves (Greenwood, Mueser, Plane, and Schlottmann 1991).…”
Section: Inter-metropolitan Mobilitymentioning
confidence: 96%